Problematika Penerapan Kegiatan Literasi di Era Pembelajaran Abad 21: Tinjauan Literatur Sistematis - Miftakhur Roifah; Hendratno, Hendratno; Subrata, Heru; Istiqfaroh, Nurul (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The implementation of literacy activities, both from government ideas and independent school ideas, is still not running optimally. This research aims to review the problems of implementing literacy activities in elementary schools. The method used in this research is Systematic Literature Review (SLR) where researchers try to collect and integrate various findings from previous research related to barriers to implementing literacy activities in elementary schools. The results of the research found general obstacles to implementing literacy activities in elementary schools, namely: (1) Lack of facilities and infrastructure to support literacy activities; (2) Lack of interest in reading by students; (3) Lack of drive for school literacy activities; (4) Lack of teacher innovation in the use of literacy learning media; and (5) Lack of parental support. Meanwhile, the solutions offered are:(1) Fulfillment of facilities and infrastructure, especially libraries and reading books; (2) Optimization of reading literacy activities 15 minutes before learning; (3) Maximizing the role of teachers as drivers of literacy activities in schools; (4) Innovation in literacy learning such as the use of media and use of technology; and (5 Maximizing the role of parents as a motivator to increase interest in reading. Based on the results and discussion that have been presented, it can be concluded that in implementing literacy activities in elementary schools there are still many problems encountered, but there are also many solutions offered.